Bilingual lexicography in the Indian sub-continent. A historical perspective of English-Hindustani/Urdu dictionary writing - Ilyas Saleem, M (2010)
The linguistic exploration in the subcontinent began with the arrival of the Europeans, i.e. Portuguese, Dutch, French and finally the British. The British established a transit trading post in the coastal city of Surat in 1608, where East India Company opened its first factory in 1612 after royal patronage was granted by the then Mughal Emperor Nuruddin Salim Jahangir. The Dutch East India Company (VOC) had already established itself in Cochin on the Malabar Coast in 1605. The Europeans were quick to identify that success in trade lay in their ability to communicate effectively in the local languages. They also identified that India was multilingual but one language practically served as lingua franca, they called it variously as Moors, Moorish, Indostan, Jargon, or Hundustani. This common vernacular was known as Hinduwee, Hindavi, Zaban-e-Hind (literally means "tongue of India"), Zaban-e-Dehli (language of Delhi), Zaban-e-Urdu-e-Mualla (means "language of the royal camp"), ultimately clipped to just Urdu/Oordoo (a Turkish word meaning a "camp or bazaar"). The roots of early bilingual lexicography lie in the development of grammar books and glossaries which started with a Dutch emissary, Joan Josua Ketelaar in 1698 (see Linguistic Survey of India, Sir George A Grierson) and continued in the form of early military grammars by Captain George Hadley (1772) and Captain James Fergusson (1773) of The British East India Company. This was followed by proper lexicographic works by several eminent scholars including J B Gilchrist, Thomas Roebuck, Dr Hunter, John Shakespeare, Duncan Forbes, and SW Fallon, and so on. In this paper I will examine the evolution of dictionary writing in the Indian subcontinent with special reference to English-Hindustani/Urdu lexicographic tradition over the past two hundred years.